Aplikasi Rantai Pasok Pada Usaha Kecil Menengah Di Kota Serdang Bedagai - Nasution, Muhammad Iqbal; Suci, Indriani; Aisyah, Siti (Jurnal Manajemen Akuntansi (JUMSI), 2022)
This study aims to explain the supply chain used by small and medium enterprises (SMEs) in Serdang Bedagai. This research is very important because SMEs help create jobs and ultimately support large companies that drive the economic growth of the country. To be able to survive in a highly competitive business environment, SMEs need to further improve their performance through supply chain management. The research method was carried out by surveying and observing the supply chain regulations of six SMEs in Serdang Bedagai. As a result, the supply chain of SMEs in Serdang Bedagai is still traditional and has a close partnership system.